A radical intermediate in tyrosine scission to the CO and CN⁻ ligands of FeFe hydrogenase - Kuchenreuther, J; Myers, W; Stich, T; George, S; NejatyJahromy, Y; Swartz, JR; Britt, R (American Association for the Advancement of Science, 2013)
The radical S-adenosylmethionine (SAM) enzyme HydG lyses free L-tyrosine to produce CO and CN− for the assembly of the catalytic H cluster of FeFe hydrogenase. We used electron paramagnetic resonance spectroscopy to detect and characterize HydG reaction intermediates generated with a set of 2H, 13C, and 15N nuclear spin-labeled tyrosine substrates. We propose a detailed reaction mechanism in which the radical SAM reaction, initiated at an N-terminal 4Fe-4S cluster, generates a tyrosine radical bound to a C-terminal 4Fe-4S cluster. Heterolytic cleavage of this tyrosine radical at the Cα-Cβ bond forms a transient 4-oxidobenzyl (4OB•) radical and a dehydroglycine bound to the C-terminal 4Fe-4S cluster. Electron and proton transfer to this 4OB• radical forms p-cresol, with the conversion of this dehydroglycine ligand to Fe-bound CO and CN−, a key intermediate in the assembly of the 2Fe subunit of the H cluster.